Øjeblikkets orgier - Overskredelseskultur, mandighed og farefuld sex i det post-socialistiske Mazambique - Groes-Green, Christian (Slagmark - Tidsskrift for idéhistorie, 2018)
In this article I explore socially marginalized young men’s excessive acts of violence, drug use, death race and unsafe sex against the background of George Bataille’s anthropology of transgression. When young men in the Mozambican capital of Maputo engage in dangerous sex or violent riots, the findings indicate, it is less a sign of ignorance about HIV or indifference towards the rule of law than an expression of living in a ‘state of emergency’ where transgressive defiance of danger and death becomeattractive. Everyday transgressions of young men who call themselves moluwene (wild, unruly) are moulded in narratives and acts which at once oppose a smouldering socialist ideology of education and a neoliberal regime exiling marginalized young men from the realm of work to permanent unemployment, poverty and orgies of the moment.